PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Afifah, Nurul; Soegiarto, Dwi (Jurnal Bulletin, 2017)
The Influence of Corporate Governance on Financial Performance in Banking Companies Listed In Indonesia Stock Exchange Year 2011-2014. This research is aimed to find the influence of corporate governance on the bankâ€™s financial perfomance. This study uses secondary dara from annual report obtained from IDX. The selection of samples is carried out by purposive sampling. Data analysis using multiple liear regression. Corporate governance consist ofÂ  board of directors, audit committee, and institusional ownership. While the measurement of financial performance is measured by Return on Equity (ROE). This research was conducted on the entire banking companies listed in Indonesia Stock Exchange 2011-2014 period. The total sample is 108 companies within four years of research. Based on the analysis results it is known that the board of directors of positive influence on the financial performance banking, and the audit committee is positive effect on the financial performance banking